Biosorption of Azo Dyes by bacterial biomass: a review - Abubakar, Abdusssamad; Yasid, Nur Adeela; Othman, Ahmad Razi; Shukor, Mohd Yunus (Hibiscus Publisher, 2023)
This review explores the potential of bacterial biomass as a sustainable and cost-effective approach for removing azo dyes from wastewater. Azo dyes, widely used in various industries, pose significant environmental challenges due to their persistence and potential toxic effects. The study provides an extensive analysis of the current literature on the biosorption of dye using bacterial biomass. It discusses the mechanisms involved in biosorption, including physicochemical interactions, microbial metabolism, and cell surface characteristics. The review presents an overview of different bacterial species, their suitability for biosorption, and the factors that influence their efficiency. The review critically evaluates various parameters affecting biosorption performance, such as pH, temperature, initial dye concentration, and biomass dosage. It highlights the importance of optimizing these parameters to enhance biosorption efficacy and maximize dye removal efficiency. The advantages and limitations of using bacterial biomass for azo dye biosorption and comparing it with other conventional treatment methods were discussed. The potential application of biosorption in large-scale scenarios and the challenges associated with its implementation are also addressed. The review emphasizes the need for further studies to explore novel bacterial strains, improve biosorption kinetics, optimize process parameters, and investigate the fate of dye-loaded biomass.